2018
DOI: 10.1016/j.bbadis.2017.11.027
|View full text |Cite
|
Sign up to set email alerts
|

FTO demethylase activity is essential for normal bone growth and bone mineralization in mice

Abstract: The Fto gene locus has been linked to increased body weight and obesity in human population studies, but the role of the actual FTO protein in adiposity has remained controversial. Complete loss of FTO protein in mouse and of FTO function in human patients has multiple and variable effects. To determine which effects are due to the ability of FTO to demethylate mRNA, we genetically engineered a mouse with a catalytically inactive form of FTO. Our results demonstrate that FTO catalytic activity is not required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 39 publications
(66 reference statements)
0
24
0
Order By: Relevance
“…Fibroblasts carrying the mutation showed impaired cell proliferation and accelerated cell senescence during culture. Developmental phenotypes of a mouse model carrying human R316Q are similar not only to the mutation‐carrying infants but also to other Fto ‐deficient mouse models, including lower body weight and lean body mass in terms of developmental aspects.…”
Section: Discussionmentioning
confidence: 71%
“…Fibroblasts carrying the mutation showed impaired cell proliferation and accelerated cell senescence during culture. Developmental phenotypes of a mouse model carrying human R316Q are similar not only to the mutation‐carrying infants but also to other Fto ‐deficient mouse models, including lower body weight and lean body mass in terms of developmental aspects.…”
Section: Discussionmentioning
confidence: 71%
“…Similar to ALKBH5, FTO is an RNA demethylase, removing the methyl group from modified adenosine . Up to now, it is known that FTO is involved in many biological processes, for example, cancer development, adipogenesis, or bone growth …”
Section: Impact Of Alkbh Proteins On Biological Processes In Higher Ementioning
confidence: 99%
“…FTO demethylation activity influences also a switch between adipogenic and osteogenic differentiation of Bone marrow‐derived mesenchymal stem cells . In later stages of growth, it sustains proper bone growth and maintains bone mass . In adult organism, FTO participates in regenerative processes following heart failure, through selective demethylation of cardiac contractile transcripts such as sarcoplasmic/endoplasmic reticulum calcium ATPase 2, myosin 6 or 7, and ryanodine receptor 2 .…”
Section: N6mea‐demethylases Participate In Cellular Regulatory Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…A 305 previous study found that Rpgrip1l mutant mouse embryos displayed facial abnormalities in cleft 306 upper lips and hypoplastic lower jaws (Delous et al, 2007). FTO demethylase activity has been found 307 essential for normal bone growth and bone mineralization in mice (Sachse et al, 2018). TBX3, a 308 member of the T-box gene family, causes Ulnar-mammary syndrome which is a rare disorder 309 characterized by distinct chin and nose shape together with many other abnormal morphological 310 changes (Bamshad et al, 1997;Joss et al, 2011).…”
mentioning
confidence: 99%